The history of nomadic societies (on the example of Kalmykia): historiographic analysis - E. N. Badmaeva (Nomadic Civilization: Historical Research)
Arch literature of Kalmyk historians, published in the 2000s, highlighting the problem of nomadic Kalmyk society. The author, exploring a large array of scientiﬁc works on this issue, focuses on the most visible works of national researchers on the nomadic Kalmyk society in modern and recent times. The study reveals their main positions, assessments and interpretations of the speciﬁcs and level of socio-historical development of nomads, the formation and establishment of Kalmyk statehood in the Asian and Russian periods of history, the complex process of including nomadic Kalmyks in the all-Russian political, legal and economic space, in general Russian-Kalmyk relations over a long historical time and other issues of Kalmyk history in the nomadic period. Based on a comparison of assessments and opinions of national authors, a critical analysis of scientiﬁc papers on this topic is given. The study concluded that the works and articles of Kalmyk historians on the nomadic Kalmyk society, using pluralism of approaches, signiﬁcantly deepened and expanded the scope of the study of the problems studied in the article.